Factors Affecting Employee Performance a Study on the Langsa City Pamong Praja and Wilayatul Hisbah Police Unit - Azura, Aya Shofia; Repina Simamora, Fitryani Melfa; Afrah, Pheby; Lusida, Novi Mutia; Ritonga, Ali Ibrahim; Yusrita, Yusrita (Mahesa Research Center, 2025)
This study aims to identify and analyze factors that affect employee performance in the Pamong Praja Police Unit (Satpol PP) and Wilayatul Hisbah (WH) Langsa City. Using a quantitative approach with a descriptive design, data was collected through a questionnaire distributed to 100 employees. The results showed that employee competence, work motivation, work discipline, leadership, organizational culture, and community support significantly affected employee performance, with an R² of 0.78. The average score for each factor was 4.2 (competence), 4.0 (motivation), 4.1 (discipline), 4.3 (leadership), 3.9 (organizational culture), and 4.1 (community support). This study found that investment in competency training, motivation development, and positive organizational culture improvement is essential to improve employee performance. In addition, community support also plays an important role in facilitating employee duties. This finding is expected to be a reference for management in formulating effective strategies to improve employee performance, so that public services in Langsa City can be improved as a whole.